2017
DOI: 10.3329/bjvm.v14i2.31411
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection and Antibiogram of Shiga Toxin Producing Escherichia Coli (Stec) Isolated From Diarrheic Children

Abstract: This study was designed to determine the shiga toxin producing genes and to investigate antibiotic sensitivity or resistant patterns of the Escherichia coli isolated from diarrheic children at Mymensingh Medical College Hospital, Bangladesh. A total of 83 stool samples were collected and screened for the detection of E. coli on the basis of cultural, staining and biochemical properties followed by molecular detection by Polymerase Chain Reaction (PCR) using genus specific 16SrRNA primers. Antimicrobial suscept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…E. coli burden in this study (24%) was comparable with the US ( Dahle et al, 2012 ), higher than Russian ( Edelstein et al, 2003 ), while lesser than reported from Bangladesh ( Islam et al, 2016 ). The variation in incidence could be due to different levels of public hygiene, climatic variation, and health education.…”
Section: Discussionsupporting
confidence: 51%
“…E. coli burden in this study (24%) was comparable with the US ( Dahle et al, 2012 ), higher than Russian ( Edelstein et al, 2003 ), while lesser than reported from Bangladesh ( Islam et al, 2016 ). The variation in incidence could be due to different levels of public hygiene, climatic variation, and health education.…”
Section: Discussionsupporting
confidence: 51%